Exploring the politicisation and territorialisation of adult social care in the United Kingdom: Electoral discourse analysis of state-wide and meso elections 1998–2019. (April 2022) - Chaney, Paul
In the face of a global demographic shift, an aging population and a 'crisis' in adult social care (ASC), this study analyses over 3000 pledges on ASC in political parties' manifesto discourse following the United Kingdom's move to a multi-level electoral politics in 1998/1999. Although often overlooked, attention to this formative phase of social policy-making reveals the discursive political antecedents of welfare interventions. The analysis shows a major increase in issue-salience and party politicisation of ASC policy. The discourse reveals political cleavages on welfare mixes and policy framing, and sub-state resistance to central government policies. Against the backdrop of the international rise of devolved governance, the present case is of wider international significance because it illustrates how the transition from state-wide to (quasi-)federal electoral practices gives rise to new territorial dynamics in the electoral discourse of welfare provision; in turn, promoting territorialisation, pressure for welfare state expansion and the rise of 'sub-state' welfare regimes.